Effect of maternal body mass index on the steroid profile in women with gestational diabetes mellitus - Sun, Yanni; Zhu, Bo; Meng, Xingjun; Yin, Binbin; Wu, Kaiqi; Liu, Yifeng; Zou, Dandan; Xue, Jianyou; Sun, Xiao; Zhang, Dan; Ma, Zhixin (Frontiers in Endocrinology, 2022)
Objective: To explore the effect of maternal body mass index (BMI) on steroid hormone profiles in women with gestational diabetes mellitus (GDM) and those with normal glucose tolerance (NGT). Methods: We enrolled 79 women with NGT and 80 women with GDM who had a gestational age of 24–28 weeks. The participants were grouped according to their BMI. We quantified 11 steroid hormones profiles by liquid chromatography-tandem mass spectrometry and calculated the product-to-precursor ratios in the steroidogenic pathway. Results: Women with GDM and BMI<25kg/m2 showed higher concentrations of dehydroepiandrosterone (DHEA) (p<0.001), testosterone (T) (p=0.020), estrone (E1) (p=0.010) and estradiol (E2) (p=0.040) and lower Matsuda index and HOMA-β than women with NGT and BMI<25kg/m2. In women with GDM, concentrations of E1 (p=0.006) and E2 (p=0.009) declined, accompanied by reduced E2/T (p=0.008) and E1/ androstenedione (A4) (p=0.010) in the BMI>25 kg/m2 group, when compared to that in the BMI<25 kg/m2 group. The values of E2/T and E1/A4 were used to evaluate the cytochrome P450 aromatase enzyme activity in the steroidogenic pathway. Both aromatase activities negatively correlated with the maternal BMI and positively correlated with the Matsuda index in women with GDM. Conclusions: NGT women and GDM women with normal weight presented with different steroid hormone profiles. Steroidogenic pathway profiling of sex hormones synthesis showed a significant increase in the production of DHEA, T, E1, and E2 in GDM women with normal weight. Additionally, the alteration of steroid hormone metabolism was related to maternal BMI in women with GDM, and GDM women with overweight showed reduced estrogen production and decreased insulin sensitivity compared with GDM women with normal weight.